Defects of non-loadbearing masonry walls due to partial basal supports - Vicente, R. Da Silva (2007)
The attempts to reduce heat transmission heterogeneity all over the external surface of building envelopes include several recommendations about external protection of concrete structures with thin clay brick walls. This procedure was extensively adopted in Portugal during the last ten years in consequence of the new national thermal code. This practice has generated several defects in consequence of the insufficient technological knowledge in this domain. This work analyses some of those defects adopting an experimental and a numerical approach, using the traditional Portuguese clay brick with a high percentage of horizontal voids.